Association Between Folic Acid Supplementation and Retinal Atherosclerosis in Chinese Adults With Hypertension Complicated by Diabetes Mellitus - Meng, Ying; Li, Jun; Chen, Xuling; She, Haicheng; Zhao, Liang; Peng, Yuan; Zhang, Jing; Shang, Kun; Li, Haibo; Yang, Wenbin; Zhang, Yadi; Gu, Xiaopeng; et al. (Frontiers in Pharmacology, 2018)
Abstract Background: This cross-section investigation included 2,199 participants with hypertension complicated by diabetes mellitus, a cohort of the China Stroke Primary Prevention Trial in which 20,702 patients with essential hypertension were given enalapril with folic acid or enalapril-only double-blind treatment for 5 years. This study aimed to explore the correlation between folic acid supplementation and retinal atherosclerosis (RA) in adults with hypertension complicated by diabetes mellitus. Methods: The diagnosis of RA was determined by non-mydriatic fundus photography and classified by the Keith-Wagener-Barker system. The statistical correlation of folic acid supplementation with RA prevalence and severity was assessed. Results: Of our cohort, 1,698 (77.6%) participants were diagnosed with RA, and the prevalence in males and females was 78.0% and 75.6%, respectively. Participants in the enalapril group had higher total homocysteine (tHcy) levels than those in enalapril–folic acid group. Compared with the enalapril group in the tHcy > 15 µmol/L group of females, the odds ratio for the enalapril–folic acid group was 0.28 (95% confidence interval, 0.11–0.67, P = 0.0061). Conclusions: The prevalence of RA was high (77.6%) in our cohort of adults with hypertension complicated by diabetes mellitus. Folic acid supplementation was significantly associated with reduced risk of RA in females with hyperhomocysteinemia. No significant association were seen in males.